Understanding the impact of in vitro transcription byproducts and contaminants - Lenk, Robin; Kleindienst, Werner; Szabó, Gábor Tamás; Baiersdörfer, Markus; Boros, Gábor; Keller, Jason M.; Mahiny, Azita J.; Vlatkovic, Irena (Frontiers in Molecular Biosciences, 2024)
The success of messenger (m)RNA-based vaccines against SARS-CoV-2 during the COVID-19 pandemic has led to rapid growth and innovation in the field of mRNA-based therapeutics. However, mRNA production, whether in small amounts for research or large-scale GMP-grade for biopharmaceutics, is still based on the In Vitro Transcription (IVT) reaction developed in the early 1980s. The IVT reaction exploits phage RNA polymerase to catalyze the formation of an engineered mRNA that depends on a linearized DNA template, nucleotide building blocks, as well as pH, temperature, and reaction time. But depending on the IVT conditions and subsequent purification steps, diverse byproducts such as dsRNA, abortive RNAs and RNA-DNA hybrids might form. Unwanted byproducts, if not removed, could be formulated together with the full-length mRNA and cause an immune response in cells by activating host pattern recognition receptors. In this review, we summarize the potential types of IVT byproducts, their known biological activity, and how they can impact the efficacy and safety of mRNA therapeutics. In addition, we briefly overview non-nucleotide-based contaminants such as RNases, endotoxin and metal ions that, when present in the IVT reaction, can also influence the activity of mRNA-based drugs. We further discuss current approaches aimed at adjusting the IVT reaction conditions or improving mRNA purification to achieve optimal performance for medical applications.